Computer system of monitoring and forecasting of water level in rivers - Horbiychuk, M.; Shufnarovych, M. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2014)
Floods and overflow forecasting is a live issue in Ukraine today. There is offered the system of monitoring and forecasting of water levels in rivers to solve this issue. The computer system enables automated acquisition of information about weather conditions and forecasts a future river level. The computer system is based on the method of mathematical models making using genetic algorithms. The use of genetic algorithms ideas for making mathematical models enables us both to choose the optimal structure for an adequate model and to reduce significantly the number of calculations when the models are iterated. The system is implemented for monitoring and forecasting of water levels in rivers of the Precarpathian region. Implementation of an automated system will reduce flood damage and improve efficiency of flood situations management.